Internal inspection of semi-transparent objects by digital holographic micro-tomography - Monroy Ramirez, F. A. (2013)
The combined use of digital holographic microscopy and computer tomography, here named digital holographic micro-tomography, is used to examine the interior of transparent channels. The proposed method is used to identify internal obstacles inside of transparent troughs having slightly different refractive index. The method is based in the acquisition of a set of digital holograms of the specimen whereas it is axially rotated from 0° to 180°. The phase differences retrieved from the obtained holograms are the inputs to a computerised axial tomography procedure. The technique has been numerically modelled in order to find the optimal tomographic conditions and also to realise the minimum difference of refractive index the method could detect. The obtained results show the feasibility of the proposed method for the non-destructive evaluation of transparent micro-objects.